1999
DOI: 10.1046/j.1439-0272.1999.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

II. The effect of p-nonylphenol on the fertility potential of male rats after gestational, lactational and direct exposure

Abstract: There is growing concern that abnormalities in male reproductive health are becoming more frequent. The most fundamental change has been the striking decline in sperm counts and semen quality. The effect of maternal exposure of rats to the oestrogenic environmental substance p-nonylphenol (p-NP) was determined in this study. Exposure to p-NP for the experimental period impaired general growth. The lower testicular mass indicated a direct toxic effect on the testis in animals exposed to p-NP during foetal life,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…De Jager et al demonstrated that the weights of the testis and epididymis were negatively affected by NP in proportion to dose [16]. Furthermore, Hossaini et al showed a dosedependent reduction in the weight of the right epididymis of male pups when dams were administered NP on days 11 to 18 of gestation at Different superscripts denote significant differences (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De Jager et al demonstrated that the weights of the testis and epididymis were negatively affected by NP in proportion to dose [16]. Furthermore, Hossaini et al showed a dosedependent reduction in the weight of the right epididymis of male pups when dams were administered NP on days 11 to 18 of gestation at Different superscripts denote significant differences (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the weight of the epididymis in rats implies a decrease in epididymal sperm density [16,20,21]. Han et al have shown that control animals have a compact and regular arrangement of cells in the seminiferous tubules, whereas animals exposed to NP display an irregular and disordered arrangement with the shedding of cellular material from the seminiferous epithelium [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, disruption of vimentin fi laments by MEHP promotes germ cell detachment due to Sertoli cells shrinking. NP administration to pregnant rats during gestation, lactancy and 10 weeks after weaning (corresponding to a complete lifespan exposed to NP) have been shown to decrease epithelial thickness, probably due to Sertoli cells shrinking and an increase in germ cell apoptosis (de Jager et al, 1999;McClusky et al, 2007). ).…”
Section: Eds Affect Spermatogenesis and Induce Germ Cell Apoptosis Inmentioning
confidence: 99%
“…A variety of stressors have been shown to inhibit spermatogenesis: hyperthermia (Lue et al, 1999;Rockett et al, 2001), anti-tumor drugs (Tates, 1992;Vecino et al, 2001), heavy metals (Bouissou and Fabre, 1966;Hew et al, 1993) and environmental hormones (de Jager et al, 1999;Raychoudhury et al, 1999) are involved in such stressors. Recent studies have noticed that heme oxygenase-1 (HO-1) and metallothionein-1/ 2 (MT-1/2) not only play roles as molecular markers for stress but are also biological defense proteins (Oguro and Yoshida, 1998;Bourdon and Blache, 2001;Suntres, 2002), because they are induced by various similar oxidative stimuli, including heat shock, heavy metals, endotoxin and cytokines, and function as a radical scavenger for reactive oxygen species (ROS) such as superoxide and hydroxyl radical produced by stress (Elbirt and Bonkovsky, 1999;Davis and Cousins, 2000).…”
Section: Introductionmentioning
confidence: 99%